" Quis custodiet ipsos custodes ?" (Juvenal Satires :§345) (Who guards [nurtures] the guardians?): Developing a constructivist approach to learning about ministerial and spiritual formation - Duncan, Graham (HTS teologiese studies, 2012)
The main purpose of this exercise was to develop an improved model of ministerial and spiritual formation in the training of ministers in the Uniting Presbyterian Church in Southern Africa at the University of Pretoria. This is a perennial problem in many churches where there is a general dissatisfaction with the products, (i.e. ministers) not only in terms of personal spirituality but in their inability to minister effectively in the many diverse situations to which they are called or appointed. The exercise of power becomes an issue in a vocation which is premised on servant ministry and so Juvenal’s quotation is apt as it is expressed as ‘Who can be trusted with authority/power?’.